Treatment of rewarming shock with PDE-inhibitors - Temperature dependent effects on transport and metabolism of cAMP and cGMP - Selli, Anders Lund (2019)
Presenation at Frampeik, Tromsø, 11-13 October 2019. Frampeik is the annual research conference for medicine and dentistry students in Norway. More information at https://www.frampeik.no/ .